Impactos do uso de aplicativos fitness por profissionais de educação física em academias de musculação de Belém do Pará - SANTOS, Rodrigo Carréra dos (2023)
The following study has as its theme the impacts of the use of fitness apps by physical education professionals in gym in Belém do Pará. It aimed to analyze the influence of applications for professionals, characterizing their use, the factors that contribute to the use of applications and whether they significantly collaborate with the professional. To this end, a survey was carried out with 12 teachers who work in gym, applying structured questionnaires, in which it was possible to measure by the Likert scale of 5 points. The results proved to be a good indicator that these digital tools are increasingly active in this sector, as well as their acceptance.